RISIKO PRODUKSI USAHATANI PADI DI KABUPATEN LAMPUNG TIMUR - Ainul Mardliyah (Journal of Food System & Agribusiness, 2018)
This research was to analyze the risk of production of paddy rice farming which received the Tertiary Irrigation (TI) optimization policy as compared to that without the Tertiary Irrigation (TI) optimization policy. This research was conducted in the village of Tulusrejo Pekalongan District of East Lampung regency. This research employed simple random sampling to collect the sample. The sample totaled 41 farmers consisting of 27 farmers who received the JIT optimization policy and 14 farmers who did not get the policy. This research was conducted from December 2016 to January 2017. Coefficient of Variation (CV) and t-test analysis were used to figure out the answer. The results showed that the risk of paddy rice production of farming which received the Tertiary Irrigation (TI) optimization policy is smaller than that which did not get the policy, although statistically it was not significantly different.Keywords: irrigation, paddy rice, the risk of production.